2016
DOI: 10.1089/met.2015.0096
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Analysis of Protein- and Carbohydrate-Focused Diets Combined with Exercise on Metabolic Syndrome Prevalence in Overweight and Obese Women

Abstract: Our findings suggest that a low-moderate calorie diet partitioned for CHO and PRO preference is equally effective when combined with a structured exercise program for reducing the prevalence of MetS prevalence in overweight/obese women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 43 publications
4
15
0
Order By: Relevance
“…A priori power calculation was set at >0.80 and was based on the observed change in fat mass between diet groups from previous research in our lab utilizing similar diet and exercise interventions [14,15,40,[42][43][44]47]. This analysis revealed that a sample size of 15-20 participants per group was sufficient to detect meaningful changes (~2 kg) in fat mass between the hypoenergetic diet (LC) groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A priori power calculation was set at >0.80 and was based on the observed change in fat mass between diet groups from previous research in our lab utilizing similar diet and exercise interventions [14,15,40,[42][43][44]47]. This analysis revealed that a sample size of 15-20 participants per group was sufficient to detect meaningful changes (~2 kg) in fat mass between the hypoenergetic diet (LC) groups.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis examining 14 studies ranging from 3-24 months in duration determined that calorie restriction is effective at reducing body weight regardless of whether the experimental diets were lower-or higher-carbohydrate diets [66]. Finally, we recently examined our own data from eight trials and determined that hypocaloric diets that were lower and higher in carbohydrate content promoted similar improvements in weight loss and metabolic syndrome scores [47]. Therefore, while it is widely debated as to whether or not low-versus high-carbohydrate diets promote greater weight loss, our data suggests that the lower-and higher-carbohydrate hypocaloric diets examined herein were equally effective at promoting weight and fat mass losses in overweight post-menopausal females that engage in exercise training.…”
Section: Secondary Outcomes-markers Of Health and Fitnessmentioning
confidence: 99%
“…A priori power calculation was set at >0.80 and was based on change in fat mass between diet groups from previous research in our lab utilizing similar diet and exercise interventions as well as considering the change in body weight reported in a similar study . This analysis revealed that a sample size of 15–20 participants per group was sufficient to detect meaningful changes in fat mass.…”
Section: Methodsmentioning
confidence: 99%
“…Our group has conducted a number of studies evaluating the effects of various diet and exercise interventions on weight loss as part of a Women's Health & Fitness Initiative . These studies generally found that participating in a circuit‐style resistance training program while following a slightly hypo‐energetic, low fat and moderately higher protein diet promoted fat loss while maintaining fat free mass and resting energy expenditure (REE) . Additionally, adherence to the moderately higher protein versions of this diet while following the circuit‐style resistance training program promoted more favourable changes in markers of metabolic syndrome .…”
Section: Introductionmentioning
confidence: 99%
“…Gregory et al [22] also showed reductions in FM while FFM was maintained during a cross-training program in non-elite trained individuals (mostly women). Even though many studies on RT with different nutritional interventions (including on lowcarbohydrate high-protein diets) have been performed in several women populations [23][24][25][26][27][28], there are a paucity of studies documenting the combined effects of KD and RT, particularly in resistance-trained women.…”
Section: Introductionmentioning
confidence: 99%